Pengelolaan Supervisi Akademik Pengawas Sekolah di Sekolah Dasar Negeri Ngadirejan Kecamatan Pringkuku Kabupaten Pacitan - Wiyono, Wiyono (Jurnal Varidika: Varia Pendidikan, 2014)
The objectives of this study are (1) to describe the implementation of the regulatory supervision of the elementary school learning activities, and (2) to describe the implications of the implementation of the regulatory supervision of the elementary school learning activities. The place of research in SDN Â Ngadirejan Pringkuku Pacitan. Collecting data using observations, interviews and documentation. Analysis using data collection, data reduction, data presentation and conclusion. The results showed that: (1) Implementation of the regulatory supervision of teaching in schools on SDN Ngadirejan are in three stages, the school superintendent supervision is based on collaboration with the principal; Problems faced by the school supervisor is supervising the status of rank, seniority and friendship. Â (2) The implications of the effectiveness of the regulatory supervision of school on school teaching are the level of preparedness of the schools, the school is very positive perception that supervisors provide assistance, guidance, direction and experience of the teacher towards professionalism and very few negative perceptions, success are achieved after supervision is the existence of physical development for the better.